Evaluating the potential effects of microplastics at environmentally realistic concentrations in South African freshwater systems - Mtintsilana, Zintle (Rhodes University, Faculty of Science, Institute for Water Research)
Microplastic pollution is spatially broad, microplastics can be found in various habitats including freshwater systems. Microplastic exposure to aquatic organisms has been associated with several physical impacts on aquatic organisms from multiple trophic levels such as; increased immune response, a decrease in food intake, excessive loss of weight, reduced growth rate, reduced energy and adverse effects on successive generations. However, these significant effects of microplastics exposure have been observed mostly in studies that use concentrations of microplastics that exceed environmental concentrations. Therefore, there is an overall lack of research on the effects of microplastics on freshwater organisms using environmentally realistic concentrations, especially in the Southern Hemisphere. A series of toxicity tests were used to expose a range of taxa including Tilapia sparrmanii, Caridina nilotica, and Melanoides tuberculata to different environmentally realistic concentrations of microplastics of different polymers. The study results show that the environmentally realistic concentrations had no statistically significant effects on most of the chosen test organisms and selected study endpoints, except for T. sparrmanii microplastic particle egestion and growth in polyethylene exposures which produced significant results. Although this study showed that at environmentally realistic concentrations and 21 days of exposure, minute effects on the test taxa were detected, various studies have proven that with longer exposure to microplastics, significant effects on freshwater organisms can be detected. Additionally, studies using concentrations higher than the current environmental concentrations have recorded significant effects on organisms and therefore, with increasing concentrations in the environment, more significant effects may be observed. Therefore, plastic pollution in the environment should be reduced as microplastics are in continuous production and circulation, and microplastic concentrations in freshwater environments are predicted to increase.
Keywords: Microplastics; Water -- Pollution; Aquatic organisms -- Effect of water pollution on